2011
DOI: 10.3109/10929088.2011.602721
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction of extremity tumor regions by CT and MRI image data fusion for subject-specific preoperative assessment and planning

Abstract: This study was conducted to demonstrate the feasibility of three-dimensional (3D) reconstruction of extremity tumor regions for patient-specific preoperative assessment and planning by using CT and MRI image data fusion. The CT and MRI image data of five patients with solid tumors were fused to construct 3D models of the respective tumor regions. The reconstruction time and image fusion accuracy were measured, and the tumor features and spatial relationships were analyzed to enable subject-specific preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It should also be noted that many authors propose PS preoperative preparation for "difficult" cases (e.g. severely comminuted fractures or cranial base tumours [49] Complete clearance of stones 5/8 (62.5%) -Mucosal perforation 1/8 (12.5%) Gateno et al [20] Deformities corrected at 6 week f/u Xia et al [27] NIP Hislop et al [44] Successful operations (0% residual vessel stenosis) 3/5 (60%) Lu et al [53] 77.8% improvement in symptoms at 9 months f/u No complications Ng et al [47] Complete resection 23/23 (100%) -4.3% had additional neurological deficit post-operatively -1/23 severely disabled due to post-operative complications Dhanda et al [17] 1.43 cm average improvement in mouth openining Fornaro et al [29] Anatomic or satisfactory reduction of fracture 7/7 (100%) -No serious complications Qiu et al [43] Total tumour resection 33/45 (73.3%) -Decrease >10% of effective fibre of pyramidal tract 7/45 (15.6%) Dong et al [28] Resection margins free of tumour in all cases Essig et al [18] 2/3 good results Ferrari et al [48] No Information Provided (NIP) Hu et al [31] NIP Tepper et al [7] NIP Derand et al [16] Surgeons' opinion: Good correlation of plan and surgical steps Calculated reduction in operation time 30min Kanzaki et al [54] No conversion to open Margins free of cancer 3 complicationsprolonged air leak, needed pleurodesis Kerens et al [33] All guides fitted well during real surgery Good stability in all cases at 6 weeks f/u No complications Nam et al [9] Good alignment of lower limb for: CAS: 92.7% -PCS:70.7% Scolozzi [25] Satisfactory reconstruction 2/2 0 complications Shen et al [37] Satisfactory or anatomical reduction in 5/6 (83.3%) cases -No complications (0%) Willaert et al [45] NIP Adolphs et al [14] NIP Desender et al [41] NIP Hsu et al [21] NIP Issa et al [32] No complications Mandel et al [57] NIP Pietsch et al [35] Satisfactory outcome (overall axis within 3 o ) 47/51 (94%) Schweizer et al [36] Improvement of wrist ROM at 1 year f/u Increase of wrist strength by 10% on average No complications (no ...…”
Section: Surgeons' Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that many authors propose PS preoperative preparation for "difficult" cases (e.g. severely comminuted fractures or cranial base tumours [49] Complete clearance of stones 5/8 (62.5%) -Mucosal perforation 1/8 (12.5%) Gateno et al [20] Deformities corrected at 6 week f/u Xia et al [27] NIP Hislop et al [44] Successful operations (0% residual vessel stenosis) 3/5 (60%) Lu et al [53] 77.8% improvement in symptoms at 9 months f/u No complications Ng et al [47] Complete resection 23/23 (100%) -4.3% had additional neurological deficit post-operatively -1/23 severely disabled due to post-operative complications Dhanda et al [17] 1.43 cm average improvement in mouth openining Fornaro et al [29] Anatomic or satisfactory reduction of fracture 7/7 (100%) -No serious complications Qiu et al [43] Total tumour resection 33/45 (73.3%) -Decrease >10% of effective fibre of pyramidal tract 7/45 (15.6%) Dong et al [28] Resection margins free of tumour in all cases Essig et al [18] 2/3 good results Ferrari et al [48] No Information Provided (NIP) Hu et al [31] NIP Tepper et al [7] NIP Derand et al [16] Surgeons' opinion: Good correlation of plan and surgical steps Calculated reduction in operation time 30min Kanzaki et al [54] No conversion to open Margins free of cancer 3 complicationsprolonged air leak, needed pleurodesis Kerens et al [33] All guides fitted well during real surgery Good stability in all cases at 6 weeks f/u No complications Nam et al [9] Good alignment of lower limb for: CAS: 92.7% -PCS:70.7% Scolozzi [25] Satisfactory reconstruction 2/2 0 complications Shen et al [37] Satisfactory or anatomical reduction in 5/6 (83.3%) cases -No complications (0%) Willaert et al [45] NIP Adolphs et al [14] NIP Desender et al [41] NIP Hsu et al [21] NIP Issa et al [32] No complications Mandel et al [57] NIP Pietsch et al [35] Satisfactory outcome (overall axis within 3 o ) 47/51 (94%) Schweizer et al [36] Improvement of wrist ROM at 1 year f/u Increase of wrist strength by 10% on average No complications (no ...…”
Section: Surgeons' Feedbackmentioning
confidence: 99%
“…A number of studies reported the cost of pre-operative preparation with PS anatomical models, ranging from hundreds to thousands pounds [14,15,25,36,54]. The manufacturing time ranged from hours to weeks [16,19,28,55].…”
Section: Surgeons' Feedbackmentioning
confidence: 99%
“…The uncertainty about the location of the tumour boundaries in the 3D virtual planning based on (CB)CT acquisitions could be eliminated by including MRI aquisitions 18 . Overlaying or fusing these MRI and (CB)CT images before the preoperative virtual planning could aid the surgeon in defining the surgical guides and subsequent reconstruction through a more accurate determination of the osteotomy location and a better understanding of the surrounding structures.…”
Section: Accepted For Publicationmentioning
confidence: 99%
“…Examples of clinical use in the 3D model are preshaping plates for minimally invasive fixation in calcaneal fracture [ 4 ], pre-operative planning for minimally invasive fixation in comminuted fracture of tibial plateau [ 5 ] and a combination of 3D printing and computer-assisted virtual surgery regarding the acetabular fracture [ 6 ]. In addition, some bone tumor cases have a soft tissue extension from the cortex; thus, mandating the use of more advanced reconstruction techniques combining computed tomography (CT) and magnetic resonance imaging (MRI) creating the subject-specific 3D model were performed [ 7 ]. Segmentations which use such fused imaging offers more accurate information than either CT or MRI alone by combining the different tissue sensitivities of each modality.…”
Section: Introductionmentioning
confidence: 99%
“…Segmentations which use such fused imaging offers more accurate information than either CT or MRI alone by combining the different tissue sensitivities of each modality. While CT images are excellent for segmenting bony structures, MRI images play a major role to segment non-bony structures [ 7 ]. Customized 3D printed implants are increasingly popular and are being currently manufactured for a variety of anatomic sites.…”
Section: Introductionmentioning
confidence: 99%